Hydroxychloroquine in patients with inflammatory and erosive osteoarthritis of the hands: results of the OA-TREAT study—a randomised, double-blind, placebo-controlled, multicentre, investigator-initiated trial. Issue 2 (2nd July 2021) - Kedor, Claudia; Detert, Jacqueline; Rau, Rolf; Wassenberg, Siegfried; Listing, Joachim; Klaus, Pascal; Braun, Tanja; Hermann, Walter; Weiner, Stefan Markus; Buttgereit, Frank; Burmester, Gerd R
Abstract : Objectives: Hand osteoarthritis (OA) is a condition characterised by cartilage degradation and frequently erosive changes. Analgesics and non-steroidal anti-inflammatory drugs are used for symptomatic relief but are often poorly tolerated or contraindicated. Previous publications suggest hydroxychloroquine (HCQ) as a possible treatment for hand OA. The OA-TREAT study aimed to investigate the efficacy and safety of HCQ in patients with inflammatory and erosive hand OA (EOA). Methods: OA-TREAT was an investigator-initiated, multicentre, randomised, double-blind, placebo (PBO)-controlled trial. Patients with inflammatory and EOA, according to the ACR criteria, with radiographically erosive disease were randomised 1:1 to HCQ 200–400 mg/day or PBO for 52 weeks (W52). Both groups received stable standard therapy. The primary endpoint was Australian Canadian Hand Osteoarthritis Index (AUSCAN) for pain and hand disability at W52. Results: 75 patients were randomised to HCQ and 78 to PBO. At W52, mean AUSCAN pain was 26.7 in HCQ and 26.5 in PBO patients (p=0.92). Hand disability measured by AUSCAN function (mean) was 48.1 in HCQ and 51.3 in PBO patients (p=0.36). Changes in radiographic scores did not differ significantly (p>0.05) between treatment groups. There were 7 serious adverse events in the HCQ and 15 in the PBO group. Conclusions: OA-TREAT is the first large randomised PBO controlled trial focusing on EOA. HCQ was no more effective than PBO for changes in pain, function and radiographic scores in the 52-week period. Overall safety findings were consistent with the known profile of HCQ.